Individualism and Nonconformity in Robert Frost’s “The Road Not Taken” - Yustisiana, Arielia; Sari, Christina Maya Iriana (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
The research entitled Individualism and Nonconformity in Robert Frost’s “The Road Not Taken” is cultural study about literature. Written in 1915 in England, "The Road Not Taken" is one of Robert Frost’s—and the world’s most well-known poems. The poem implicitly delved individualism and nonconformity. The poem can be interpreted as a critique of people’s propensity to second-guess their decisions and think that they would have turned out better. It poses doubts regarding the influence of personal decisions on a person’s life journey and casts doubt on the idea that one path is fundamentally superior than another. Therefore, it became the topic to discuss. It was revealed using poetic devices, that is, metaphor and symbols. Metaphor and symbol are included in sense devices, therefore the theory of figure of speech was used. In order to verbalize individualism and nonconformity in the poem, theory of identity from Stryker (1980) was useful. It was descriptive research and there were two literary approaches used in the research, structural and formalistic approach. It was found that the speaker in the poem, faced with a choice between two roads, takes the road "less travelled," a decision which he or she supposes "made all the difference." The poem beautifully explores the idea of individualism and nonconformity by presenting the choice of a diverging road as a metaphor for life’s decisions. The poem encourages readers to embrace their unique identities and make choices that align with their values, even if it means going against societal norms. It celebrates the importance of personal agency and the transformative power of unconventional choices.